2004
DOI: 10.1051/forest:2004039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of defoliation on the frost hardiness and the concentrations of soluble sugars and cyclitols in the bark tissue of pedunculate oak (Quercus robur L.)

Abstract: -As a measure of frost hardiness, we determined an index of injury (I -30 ) in living bark tissue of 20-year-old pedunculate oaks (Quercus robur L.) that had been manually and almost completely defoliated in the first half of May of one or two years, and of non-defoliated control trees. I -30 was calculated as a percentage value on the basis of electrolyte leakage from samples artificially frozen at a temperature of -30°C, and from unfrozen control samples. In parallel, the bark's concentrations of soluble su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 34 publications
(46 reference statements)
3
12
0
Order By: Relevance
“…Seasonal changes in cold hardiness represented by LT 50 values were strongly correlated to total soluble sugar content in both cultivars (Table 1), as shown by many previous studies (Améglio et al, 2004;Morin et al, 2007;Palonen et al, 2000;Thomas et al, 2004). Sugars play an important role in plant growth and development under abiotic stress by regulating carbohydrate metabolism (Gupta and Kaur, 2005).…”
Section: Discussionsupporting
confidence: 49%
“…Seasonal changes in cold hardiness represented by LT 50 values were strongly correlated to total soluble sugar content in both cultivars (Table 1), as shown by many previous studies (Améglio et al, 2004;Morin et al, 2007;Palonen et al, 2000;Thomas et al, 2004). Sugars play an important role in plant growth and development under abiotic stress by regulating carbohydrate metabolism (Gupta and Kaur, 2005).…”
Section: Discussionsupporting
confidence: 49%
“…Thomas et al (2002) developed a model, based on experimental work in controlled conditions and on mature trees at several sites experiencing decline, that explains interactions among abiotic and biotic factors involved in oak decline in Central Europe. They theorized that the physiological effects of defoliation on oaks render them more susceptible to climate extremes, such as drought and frost Gieger and Thomas, 2002;Thomas et al, 2004;Marçais and Bréda, 2006). Specifically, they suggested that depletion of C reserves impairs fine-root production, through loss of photosynthetic surface area and reduced rates of photosynthesis (evidenced by reduced stomatal conductance) (e.g.…”
Section: Secondary Factorsmentioning
confidence: 98%
“…Frost and Hunter, 2008). Reduced fine-root biomass limits water uptake during drought, and along with cavitation (breakage of the water column in xylem vessels) leading to embolism (formation of air bubbles in the xylem) caused by drought or damaging frost, severely compromises oak water relations (Gieger and Thomas, 2002;Thomas et al, 2004). Secondary agents, usually A. biguttatus and/or root pathogens, then attack/infect and kill the weakened oaks.…”
Section: Secondary Factorsmentioning
confidence: 99%
“…A warmer October may, therefore, result in more carbohydrates being relocated to perennial tissues, making more nutrient and energy reserves available for growth during the next season. In addition, since the amount of non-structural carbohydrates in plant tissues is generally linked to the degree of frost tolerance (Parker, 1967;Sakai and Larcher, 1987;Thomas et al, 2004), a higher degree of translocation may increase the resistance of oak trees to low temperatures. A similar positive relationship between growth and previous October temperature was reported in pedunculate oaks in England (Fletcher, 1974).…”
Section: Growth and Monthly Weather Conditionsmentioning
confidence: 99%